Bridging Healthcare and Technology: Management Systems in Radiology Services - Finny Rizki Putri; Charles Ayodeji Osunla; Rahul Argha Sen (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: The purpose of this study was to determine the description of the implementation of the Hospital Management Information System at the Radiology Installation of Dr. M. Yunus Bengkulu Regional General Hospital. Methodology: This research was conducted using a qualitative descriptive approach because it will describe the activities that occur in the implementation of the Hospital Management Information System in the Radiology Installation in the field in more depth. Main Findings: In its implementation, the Hospital Management Information System at the dr. M. Yunus Regional General Hospital including the Radiology installation has been running in accordance with the Minister of Health Regulation No. 1171/MENKES/PER/2011, however, in its implementation there are still several things that have not been implemented such as the absence of policies related to the implementation of the Management Information System at the Radiology installation, the absence of written policies related to routine meetings, inadequate networks, reporting applications that are not yet available, and maintenance of facilities and infrastructure. In addition, in its implementation there is also no reporting of indicators and written procedures related to data management. Meanwhile, in its implementation, data consistency is not a problem because the data obtained is based on patient examinations every day. Novelty/Originality of this study: This study reveals the dynamics and challenges of implementing the Hospital Management Information System in the Radiology Installation of Dr. M. Yunus Regional General Hospital, Bengkulu, which can be the basis for developing a more effective and local-appropriate information system.